2020
DOI: 10.1103/physrevlett.124.173203
|View full text |Cite
|
Sign up to set email alerts
|

Nematic-Orbit Coupling and Nematic Density Waves in Spin-1 Condensates

Abstract: We propose the creation of artificial nematic-orbit coupling in spin-1 Bose-Einstein condensates, in analogy to spin-orbit coupling. Using a suitably designed microwave chip the quadratic Zeeman shift, normally uniform in space, can be made to be spatially varying, leading to a coupling between spatial and nematic degrees of freedom. A phase diagram is explored where three quantum phases of the nematic order emerge: easy-axis, easy-plane with single-well and easy-plane with double well structure in momentum sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Several authors have suggested a connection between spinor gases with spin-changing collisions and SOC BECs [37][38][39][40][41][42][43][44]. In this work, we show analytically that the Raman-dressed spin-1 SOC gas at low energy is equivalent, for weak Raman coupling and interactions, and zero total magnetization, to an artificial spin-1 gas with tunable spin-changing collisions.…”
mentioning
confidence: 55%
“…Several authors have suggested a connection between spinor gases with spin-changing collisions and SOC BECs [37][38][39][40][41][42][43][44]. In this work, we show analytically that the Raman-dressed spin-1 SOC gas at low energy is equivalent, for weak Raman coupling and interactions, and zero total magnetization, to an artificial spin-1 gas with tunable spin-changing collisions.…”
mentioning
confidence: 55%
“…Several authors have suggested a connection between spinor gases with spin-changing collisions and SOC BECs [12,[25][26][27][28][29][30][31]. In this work, we show analytically that the Raman-dressed spin-1 SOC gas at low energy is equivalent, for weak Raman coupling and interactions, and zero total magnetization, to an artificial spin-1 gas with tun- able spin-changing collisions.…”
mentioning
confidence: 56%
“…Apart from various novel ground states such as half-quantum vortex [5][6][7][8], stripe phase [6,[9][10][11][12][13][14][15][16]and vortex related structures [17,18], the introduction of SO coupling has led to many other possibilities of topological textures including skyrmions [17,[19][20][21], meron [22][23][24] and monopoles [25,26]. Recently, relevant work has been extended to SO induced supersolid phase [27][28][29], spintensor-momentum coupling [30] , spin-nematic-orbit coupling [31] and another fundamental type, namely, the coupling between spin and orbital angular momentum of atoms [32,33], where phenomena like the splitting of vortex cores [34] and the first-order phase transitions [35] have been observed experimentally.…”
Section: Introductionmentioning
confidence: 99%